Frustration wave order in iron(II) oxide spinels. Issue 1 (December 2018) - Perversi, Giuditta; Arevalo-Lopez, Angel; Ritter, Clemens; Attfield, J.
Abstract Frustrated magnetic materials can show unconventional correlations such as quantum spin liquid states and monopole excitations in spin ices. These phenomena are observed on uniformly frustrated lattices such as triangular, kagome or pyrochlore types, where all nearest neighbour interactions are equivalent. Here we report incommensurate long-range spin amplitude waves in the spinels Fe2 GeO4 and γ-Fe2 SiO4 at low temperatures, which indicate that the degree of frustration may itself be a fluctuating quantity that can spontaneously order without a lattice distortion as a 'frustration wave'. Fe2 GeO4 with propagation vector (2 /3  + δ 2 /3  + δ 0) has ordered Fe2+ moments that vary between fully saturated 4 μB and 0 values, consistent with a frustration wave order. γ-Fe2 SiO4 has a more complex (¾ + δ ¾ + δ 0) order that coexists with an ordered spin ice phase. Dynamic orbital fluctuations are proposed to give rise to locally correlated patterns of ferromagnetic and antiferromagnetic interactions consistent with the observed orders. Frustrated magnetic materials provide a great laboratory to study the interplay between classical order and quantum fluctuations. The authors study the frustrated magnetic ground states of two Fe spinel oxides showing that the frustration is a fluctuating characteristic that manifests itself as a "frustration wave"